Genomics 101: an introduction to sequencing - Yeo, Giles (Henry Stewart Talks, 2021)
Sanger sequencing, Fluorescent Sanger sequencing, Whole genome sequencing, Next generation sequencing, Multiplexing, Whole exome sequencing, Transcriptome sequencing, Chromatin immunoprecipitation sequencing